2009
DOI: 10.1073/pnas.0901986106
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of metals from supercritical fluids

Abstract: Electrodeposition is a widely used materials-deposition technology with a number of unique features, in particular, the efficient use of starting materials, conformal, and directed coating. The properties of the solvent medium for electrodeposition are critical to the technique's applicability. Supercritical fluids are unique solvents which give a wide range of advantages for chemistry in general, and materials processing in particular. However, a widely applicable approach to electrodeposition from supercriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 29 publications
0
84
0
Order By: Relevance
“…Organic co-solvents form a single phase with scCO 2 and considerably improve the solubility of ionic species. This mixed solvent phase has been largely documented in the field electrodeposition [3,18,22], with Bartlett et al recently reviving interest in SCFs as electroplating media. Their research efforts have demonstrated that the unique mass transport properties and lack of surface tension in supercritical media permit the formation of well-defined nano-structured electrodeposits [3].…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 99%
“…Organic co-solvents form a single phase with scCO 2 and considerably improve the solubility of ionic species. This mixed solvent phase has been largely documented in the field electrodeposition [3,18,22], with Bartlett et al recently reviving interest in SCFs as electroplating media. Their research efforts have demonstrated that the unique mass transport properties and lack of surface tension in supercritical media permit the formation of well-defined nano-structured electrodeposits [3].…”
Section: Supercritical Carbon Dioxide (Scco 2 )mentioning
confidence: 99%
“…In general, it is understood that the better electrolytes for scCO 2 electrochemistry are highly fluorinated salts and consist of bulky ions. Anions such as tetrakis(pentafluorophenyl)borate (TFPB À ) and tetrakis(3,5-trifluoromethyl phenyl)borate are often used in liquid-liquid electrochemistry to pump protons from a water phase into an organic phase, 12,13 but have also been applied to scCO 2 electrodeposition processes as reported recently by Bartlett et al [14][15][16] In 1996, Abbott and co-workers 17 reported the high solubility of long chain ammonium alkanes in non-polar solvents, presenting tetra(decyl)ammonium tetraphenylborate (TDATPB) as a suitable electrolyte for scCO 2 studies. 5 Chanfreau et al used the latter electrolyte more recently in the electrocarboxylation of benzyl chloride in pressurised CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…This cell is specially designed and has been described in the literature [32]. The steel cell consists of two parts, the top part contains seven 1/16 inch female SSI type fittings through which a thermocouple, a CO 2 /R32 feeding line and the 5 electrodes could be fed and sealed.…”
Section: Cell Designmentioning
confidence: 99%